Evaluating hot mix asphalt for different recycled asphalt pavement contents and filler kinds utilizing marshall characteristics and moisture damage - Hawraa Jabbar; Miami Hilal; Mohammed Fattah (Engineering and Technology Journal)
A significant amount of reclaimed asphalt pavement must be used to address the growing demand for sustainable road-building materials. One of the problems of employing RAP in mixes is that it makes them more rigid. The guideline specifies that when the amount of RAP is greater than 15%, softer-grade asphalt should be used; however, the asphalt used in Baghdad is 40–50 grade, and its high viscosity makes it challenging to mix when adding RAP. Sometimes, softer grades are not readily available and must be made upon request. Therefore, using some waste oil as a rejuvenator was the task. It is more economical and environmentally friendly. In this study, three asphalt grades (40-50, 60-70, and 85-100) are used, and three distinct types of fillers; hydrated lime, Portland cement, and limestone dust; with an aggregate gradation of maximum size (12.5 mm). Three percentages of recycled asphalt pavement (RAP) materials, 10%, 20%, and 30%, are used. Based on Marshal graphs, the optimum asphalt cement content for each grade was calculated. The samples in all blends were subjected to volumetric analysis, Marshall Stability, flow, and water sensitivity testing. The findings of this study showed that adding hydrated lime enhanced Marshall properties and reduced the sensitivity of asphalt mixes to moisture. Stability increases as the proportion of RAP increases. Asphalt (40-50) with 4% waste oil showed improved stability than the original asphalt mix and presented better Marshall properties than the softer grade (85-100). Additionally, mixes containing RAP may be less moisture-resistant than conventional mixtures.